(untitled) (Global Journal of Management and Business Research, 2014)
The purpose of this study is to investigate the inter-sectoral linkages and the effects of each sector onother sectors in Jordanian economy by using Input and output tables for the years : 1987, 2000, and 2009.To facilitate the comparison process between sectors the researcher assembled and aggregated the each table to 15 sectors. This study applied Input and Output technique to determine the leader sector which has highest backward and forward linkages.